Immune Effects of Macrophages in Rheumatoid Arthritis: A Bibliometric Analysis From 2000 to 2021 - Xu, YunLing; Zhang, Zhongmin; He, Jiaolong; Chen, Zhenxing (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by macrophage activation. The current characteristics, hotspots, and research frontiers of macrophage-related RA were analyzed using bibliometric analysis. Relatedpapers published from 2000 to 2021 in the Web of Science database were retrieved. The diagrams were generated and analyzed using the bibliometric software package. VOSviewer and CiteSpace were used to evaluate and visualize the research trends and hotspots in macrophage-related RA. A total of 7253 original articles were obtained. Global research on macrophage-related RA is in an advanced stage of development, with core authors, teams and research institutions emerging. United States has published the most papers, received the most citations, and had the highest H-index over the last 22 years. The University of Amsterdam and the journal of Arthritis and Rheumatism are the most productive research institutions and journals. Tak PP’s (St Vincent’s Hospital) paper has the highest publication and citation scores. The keywords “bone loss” and “polarization” have the highest frequency. Additionally, the study of macrophage polarization in RA has been research focus in recent years. This study demonstrates that research on macrophages in RA will continue. China is a significant producer, whereas the United States is an influential nation in this regard. In the last decade, most studies have concentrated on fundamental research. Recent studies have shown how macrophages play a role in controlling and weakening inflammation, and drug delivery and mechanism have come to the fore.